Hubungan Fungsi Kognitif Dengan Kemandiran Dalam Aktivitas Sehari-Hari Pada Lansia di Kelurahan Palangka Kota Palangka Raya - Putria Carolina; Takesi Arisandy (Jurnal Kesehatan Saelmakers PERDANA, 2023)
Elderly is a group of people aged 60 years and over, the increasing elderly population will increase new problems in various fields. Decline in cognitive function is the main cause of the dependence of the elderly on other people so that the quality of life of the elderly is assessed by the independence of daily activities in the elderly so that it can be interpreted that cognitive function is related to independence in daily activities in the elderly. This study aims to determine the relationship between cognitive function and independence in daily activities in the elderly in the work area of ??Palangka Village, Palangka Raya City. The research design uses a quantitative method with a correlational type of research using a cross-sectional approach. This data collection uses a questionnaire measurement tool, then the data is analyzed using the spearman rank (rho) statistical test. The sample in this study were 48 elderly people consisting of 26 men and 22 women. The results showed a significant p value <? with a significant level of ? = 0.05. A significant value using the spearman rank (rho) statistical test was obtained Asmp. Sig. (2 tailed) of 0.000. The results of this study indicate that there is a relationship between cognitive function and independence in daily activities for the elderly in Palangka Village, Palangka Raya City.